Achieving universal health coverage in India: a scoping review on the requisite public health actions - Avani Radheshyam; Vinod K. Ramani; Radheshyam Naik (Frontiers in Public Health)
IntroductionIn India, large inequities in health exist by geography, gender, socio-economic class, religion and caste. Universal health coverage (UHC) is envisioned to address these gaps. The deficiencies in our healthcare system cannot be solely bridged by additional investment, increasing manpower, adoption of technology or establishing regulatory Institutes. While UHC offers promise, its nation-wide implementation must be carefully planned and monitored.Objectives(1) To review published literature appraising the concepts of UHC such as coverage of health services and financial protection in the Indian healthcare system, (2) To review the deficiencies of the healthcare system in India and explore solutions within the framework of UHC.MethodsThe relevant articles for review were retrieved from PubMed and Google scholar databases using pertinent text terms. This scoping review includes 12 citations and 3 other published reports which address the determinants of UHC and its impact on the healthcare system in India.ResultsUHC aims to address the concept of health in all its dimensions and not merely as a response to illness. This Program’s objectives include reducing the gap between the need and utilization of healthcare, improving its quality and providing financial protection. In India, the public health sector suffers from shortfalls in management, manpower issues and poor accountability, whereas the private health sector is unregulated and contributes to the increasing health expenditure. UHC will improve access to health care and prevent financial impoverishment, which will be advantageous to the rural people and urban poor including workers of the unorganized sector.ConclusionUHC enables health systems to efficiently deliver a wide range of healthcare services to the population, as well as adopt sustainable financing mechanisms. Given the current Covid-19 pandemic and the need to address future pandemics, we need to build resilient health systems as well as hasten the implementation of UHC.